Ferritic stainless steel sheet and method for producing same

By controlling the crystal particle size of the ferrite stainless steel plate and adjusting the steel composition, a two-phase structure of ferrite phase + austenite phase is formed, and the problems of insufficient toughness and poor corrosion resistance of the ferrite stainless steel plate under low temperature conditions are solved, and the effects of high toughness and corrosion resistance are achieved.

CN119615019APending Publication Date: 2025-03-14JFE STEEL CORP

Patent Information

Application Number
CN202411652503.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2017-10-30
Filing Date
2018-10-16
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing ferritic stainless steel plates are not tough enough under low temperature conditions, which leads to prone to rupture when manufacturing the flange and have poor corrosion resistance.

Method used

By controlling the average crystal particle size of the metal structure to be less than 45 μm, the content of steel components such as Si, Mn, Cr, and Ni is adjusted, and hot-rolled and hot-rolled plate annealing is carried out after heating at 1050 to 1250°C to form a two-phase structure of ferrite phase + austenite phase to improve toughness and corrosion resistance.

Benefits of technology

High toughness under -50°C conditions is achieved, cracking during flange processing is avoided, and rust rate is maintained in the brine spray cycle test, which significantly improves corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005141325000000141
    Figure BDA0005141325000000141
  • Figure BDA0005141325000000151
    Figure BDA0005141325000000151
Patent Text Reader

Abstract

Provided are: a ferritic stainless steel sheet having a component composition containing, in mass%, 0.001 to 0.020% of C, 0.05 to 0.35% of Si, 0.05 to 1.00% of Mn, 0.04% or less of P, 0.01% or less of S, 0.001 to 0.300% of Al, 10.0 to 13.0% of Cr, 0.75 to 1.50% of Ni, 0.05 to 0.35% of Ti, and 0.001 to 0.020% of N, and having a [gamma] I [%] composed of formula (1) of 65% or more; the remainder comprises Fe and unavoidable impurities, and the average crystal grain size of the metallographic structure is 45 [mu] m or less. [gamma] I [%] = 24Ni + 12Mn + 6Cu-18Si-12Cr-12Mo + 188 (1). In formula (1), Ni, Mn, Cu, Si, Cr, and Mo represent the content (mass%) of each component, and the content of the component not contained is 0.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of patent application 201880070416.7 (International application date: International application date: October 16, 2018, Invention name: Ferritic stainless steel plate and manufacturing method thereof). Technical Field

[0002] The present invention relates to a ferritic stainless steel sheet and a method for producing the same, and more particularly to a ferritic stainless steel sheet which is useful for flange parts and has excellent toughness and corrosion resistance, and a method for producing the same. Background Art

[0003] The exhaust path of a car is composed of various components such as an exhaust manifold, a muffler, a catalyst, a flexible pipe, a center pipe, and a front pipe. When connecting these components, a fastening component called a flange is often used. The flange used in such an exhaust system component needs to have sufficient rigidity. Therefore, a thick-walled flange (for example, a plate thickness of 5 mm or more) is applied to such an exhaust system component.

[0004] In addition, the flange is manufactured by punching or the like in addition to press forming, and ordinary steel can be used.

[0005] Furthermore, in recent years, sufficient corrosion resistance is required for flange materials used in parts exposed to high-temperature exhaust gas in the EGR (Exhaust Gas Recirculation, EGR) system. Therefore, the use of stainless steel, which has excellent corrosion resistance compared to ordinary steel, and ferritic stainless steel, which has a small thermal expansion coefficient and is less likely to generate thermal stress, is being studied. As a result, there is a strong demand for ferritic stainless steel sheets with a large plate thickness (for example, a plate thickness of 5 mm or more) that can be used for thick-walled flanges.

[0006] However, thick ferritic stainless steel has a problem of low temperature toughness. For example, stress cracking during flange manufacturing occurs frequently in winter. Therefore, there is a strong demand for improvement in the toughness of thick ferritic stainless steel.

[0007] In response to such market demands, for example, Patent Document 1 discloses a toughness (Charpy impact value at -40°C is 50 J / cm 2The stainless steel sheet is characterized in that, in terms of mass%, it contains C: 0.02% or less, N: 0.02% or less, Si: 0.005-1.0%, Ni: 0.1-1.0%, Mn: 0.1-3.0%, P: 0.04% or less, S: 0.0100% or less, Cr: 10% or more and less than 18%, and further contains one or two of Ti: 0.05-0.30%, and Nb: 0.01-0.50%, the total of Ti and Nb is 8 (C + N) to 0.75%, and the remainder is composed of Fe and unavoidable impurities, γ p The content of the ferrite is 70% or more, the ferrite grain size is 20 μm or less, and the amount of martensite generated is 70% or less.

[0008] It should be noted that γ p (%) was evaluated using the following formula (i) (expressed as formula (1) in Patent Document 1).

[0009] γ p =420(%C)+470(%N)+23(%Ni)+9(%Cu)+7(%

[0010] Mn)-11.5(%Cr)-11.5(%Si)-12(%Mo)-23(%V)-47(%Nb)-49(%Ti)-52(%Al)+189(i)

[0011] In addition, (%X) represents the mass ratio of each component X.

[0012] Prior art literature

[0013] Patent Literature

[0014] Patent Document 1: Japanese Patent Application Publication No. 2016-191150. Summary of the invention

[0015] However, the inventors of the present invention tried to use the stainless steel plate described in Patent Document 1 to process it into a thick-walled flange shape with a flanging portion, and found that cracks occurred in the flanging portion and the specified flange shape could not be obtained. Therefore, it is not suitable for thick-walled flanges.

[0016] In view of the above circumstances, an object of the present invention is to provide a ferritic stainless steel sheet having further improved toughness and excellent corrosion resistance, and a method for producing the same.

[0017] In the present invention, "excellent toughness" means that the Charpy impact value at -50°C is 100 J / cm 2 In the present invention, excellent corrosion resistance means that the rust rate after three cycles of the salt spray cycle test specified in JIS H 8502 is 25% or less.

[0018] The present inventors conducted detailed studies to solve the above problems and found the following.

[0019] In order to process a thick flange with a flanged portion without causing cracks, it is effective to refine the metal structure and reduce the Charpy impact value at -50°C to 100 J / cm 2 Specifically, by making the average crystal grain size of the metal structure 45 μm or less, the occurrence of cracks in the flanged portion when processing into a thick flange with a flanged portion can be effectively suppressed, and the present invention can be fully applicable to a thick flange with a flanged portion.

[0020] In order to refine the metal structure and obtain a Charpy impact value of 100 J / cm at -50°C, 2 As described above, it is effective to heat a billet having an appropriate steel component, specifically a steel component composition in which Si, Mn, Cr, Ni, etc. are controlled within an appropriate range, at 1050 to 1250°C, perform hot rolling, and anneal the hot-rolled sheet at an appropriate temperature.

[0021] The present invention has been made in view of the above circumstances, and the gist of the present invention is as follows.

[0022] [1] A ferritic stainless steel sheet having the following composition: containing, by mass%, C: 0.001 to 0.020%, Si: 0.05 to 0.35%, Mn: 0.05 to 1.00%, P: 0.04% or less, S: 0.01% or less, Al: 0.001 to 0.300%, Cr: 10.0 to 13.0%, Ni: 0.75 to 1.50%, Ti: 0.05 to 0.35%, N: 0.001 to 0.020%, and a γ-ray diffraction reaction system having the following formula (1): I [%] is 65% or more, the remainder is composed of Fe and inevitable impurities, and the average crystal grain size of the metal structure is 45 μm or less.

[0023] γ I [%]=24Ni+12Mn+6Cu-18Si-12Cr-12Mo+188 (1)

[0024] In addition, Ni, Mn, Cu, Si, Cr and Mo in Formula (1) represent the content (mass %) of each component, and the components not contained are represented by 0.

[0025] [2] The ferritic stainless steel sheet according to [1] above, further comprising, in addition to the above component composition, one or more of Cu: 0.01 to 1.00%, Mo: 0.01 to 1.00%, W: 0.01 to 0.20%, and Co: 0.01 to 0.20%, in terms of mass%.

[0026] [3] The ferritic stainless steel sheet according to [1] or [2], further comprising, in addition to the above component composition, one or more of V: ​​0.01 to 0.20%, Nb: 0.01 to 0.10%, and Zr: 0.01 to 0.20%, in terms of mass%.

[0027] [4] The ferritic stainless steel sheet according to any one of [1] to [3] above, further comprising, in addition to the above component composition, one or more of the following, calculated by mass %, including 0.001% to 0.100% REM, 0.0002% to 0.0025% B, 0.0005% to 0.0030% Mg, and 0.0003% to 0.0030% Ca.

[0028] [5] A method for producing a ferritic stainless steel sheet, which is the method for producing a ferritic stainless steel sheet according to any one of [1] to [4], comprising a hot rolling step of heating a steel slab having the above composition at 1050 to 1250°C and then hot rolling the steel slab; and a hot rolled steel sheet annealing step of annealing the hot rolled steel sheet obtained in the hot rolling step at 750 to 1050°C.

[0029] According to the present invention, a ferritic stainless steel sheet having better toughness and excellent corrosion resistance is obtained. The ferritic stainless steel sheet of the present invention can be suitably used for applications such as thick flanges. DETAILED DESCRIPTION

[0030] Hereinafter, the present invention will be described in detail.

[0031] The inventors of the present invention have studied in detail the detailed causes of cracking when forming a flange hole of 30 mmφ from the surface of the steel sheet in the blank state (after punching) into a flange with a 10 mm upwardly raised flanged portion using various ferritic stainless steel sheets with a thickness of 5.0 mm. The results show that the Charpy impact value at -50°C is 100 J / cm 2 The above steel plates do not crack, and the Charpy impact value of the cracked steel plates at -50°C is less than 100 J / cm 2 . It can be seen that low toughness is the cause of the cracks.

[0032] In addition, the inventors of the present invention have studied in detail the relationship between the low toughness and the metal structure. As a result, it can be seen that the larger the average crystal grain size of the steel plate, the lower the toughness. Therefore, various ferritic stainless steel plates (plate thickness 5.0 mm) were used to try to form the above-mentioned flange. As a result, it can be seen that the toughness of steel plates with an average crystal grain size greater than 45 μm is reduced and cracks are easily generated. If the average crystal grain size is less than 45 μm, the toughness is excellent and the punching processability of the steel plate is good.

[0033] As described above, in the present invention, the average crystal grain size is 45 μm or less, and the Charpy impact value at -50°C is 100 J / cm 2 above.

[0034] The average crystal grain size can be measured by the measuring method in the examples described below. As described below, the Charpy impact value is a value measured in accordance with JIS Z2242 (2005).

[0035] Next, the component composition of the ferritic stainless steel sheet of the present invention will be described.

[0036] Hereinafter, the unit "%" as the content of a component means "mass %" unless otherwise specified.

[0037] C: 0.001~0.020%

[0038] If the C content exceeds 0.020%, the processability and corrosion resistance will be significantly reduced. From the viewpoint of corrosion resistance and processability, it is preferred that the C content is as low as possible. When the C content is less than 0.001%, refining will take time, which is not preferred in terms of manufacturing. Therefore, the C content is in the range of 0.001% to 0.020%. The C content is preferably 0.003% or more, and more preferably 0.004% or more. In addition, the C content is preferably 0.015% or less, and more preferably 0.012% or less.

[0039] Si: 0.05~0.35%

[0040] Si is an element that has the effect of improving the corrosion resistance of the weld by forming an oxide film concentrated during welding and is useful as a deoxidizing element in the steelmaking process. These effects are obtained by containing more than 0.05% Si, and the higher the content, the better the effect. On the other hand, Si has the effect of promoting the formation of ferrite phase. If the Si content exceeds 0.35%, the specified amount of austenite phase is not fully generated during heating in the hot rolling process. Therefore, even if hot rolling and hot rolled sheet annealing are performed under the conditions specified in the present invention, the desired metal structure cannot be obtained. Therefore, the Si content is 0.05% to 0.35%. The Si content is preferably 0.10% or more. In addition, the Si content is preferably 0.30% or less.

[0041] Mn: 0.05~1.00%

[0042] Mn has the effect of promoting the formation of austenite phase. In order to obtain this effect, it is necessary to contain 0.05% or more of Mn. However, if the Mn content exceeds 1.00%, the precipitation of MnS, which becomes the starting point of corrosion, is promoted, and the corrosion resistance is reduced. Therefore, the Mn content is 0.05% to 1.00%. The Mn content is preferably 0.20% or more. In addition, the Mn content is preferably 0.80% or less, and more preferably 0.70% or less.

[0043] P: 0.04% or less

[0044] P is an element inevitably contained in steel and is harmful to corrosion resistance and workability, so it is preferably reduced as much as possible. If the P content exceeds 0.04%, the workability is significantly reduced due to solid solution strengthening. Therefore, the P content is 0.04% or less. The P content is preferably 0.03% or less.

[0045] S: 0.01% or less

[0046] S is an element that is inevitably contained in steel, just like P. It is an element that is harmful to corrosion resistance and workability, so it is preferably reduced as much as possible. In particular, if the S content exceeds 0.01%, the corrosion resistance is significantly reduced. Therefore, the S content is 0.01% or less. The S content is preferably 0.008% or less, and more preferably 0.003% or less.

[0047] Al: 0.001~0.300%

[0048] Al is an effective deoxidizer. Al has a stronger affinity for nitrogen than Cr, so when nitrogen invades the weld, nitrogen is precipitated as Al nitrides rather than Cr nitrides, which has the effect of suppressing sensitization. These effects are obtained by containing 0.001% or more of Al. However, if more than 0.300% of Al is contained, the penetration during welding is reduced and the weldability is reduced, which is not preferred. Therefore, the Al content is in the range of 0.001% to 0.300%. The Al content is preferably 0.010% or more. In addition, the Al content is preferably 0.200% or less, more preferably 0.100% or less, and further preferably 0.050% or less.

[0049] Cr: 10.0~13.0%

[0050] Cr is the most important element for ensuring corrosion resistance. If its content is less than 10.0%, the corrosion resistance required for automobile exhaust parts cannot be obtained. On the other hand, if the Cr content exceeds 13.0%, even if the steel composition is adjusted to the γ I, the specified amount of austenite phase is not generated during heating in the hot rolling process, so even if hot rolling and hot rolled sheet annealing are performed under the conditions specified in the present invention, the desired metal structure cannot be obtained. Therefore, the Cr content is in the range of 10.0% to 13.0%. The Cr content is preferably 10.5% or more. In addition, the Cr content is preferably 12.0% or less, and more preferably 11.7% or less.

[0051] Ni: 0.75-1.50%

[0052] Ni is an austenite-generating element and has the effect of increasing the amount of austenite generated during heating before rolling in the hot rolling process. In the present invention, by adjusting the steel composition, the billet in the hot rolling process contains a two-phase structure of ferrite phase + austenite phase with a volume ratio of 70% or more austenite phase when heated. When the metal structure is a two-phase structure of ferrite phase + austenite phase, the heterophase interface between the ferrite phase and the austenite phase functions as a barrier to grain growth, so the metal structure before hot rolling is refined. Therefore, the processing deformation that becomes a recrystallization site is accumulated by the prescribed hot rolling, and recrystallization is generated by annealing the hot rolled sheet in the subsequent process, thereby obtaining a fine metal structure and showing excellent toughness. These effects are obtained by containing more than 0.75% Ni. On the other hand, if the Ni content exceeds 1.50%, the improvement effect brought about by the refinement of the grains is saturated, and the workability is reduced. In addition, stress corrosion cracking is easily generated. Therefore, the Ni content is 0.75% to 1.50%. The Ni content is preferably 0.80% or more. Furthermore, the Ni content is preferably 1.20% or less, and more preferably 1.00% or less.

[0053] Ti: 0.05~0.35%

[0054] Ti has the effect of preferentially combining with C and N to inhibit the precipitation of Cr carbonitrides, lowering the recrystallization temperature, and inhibiting the reduction in corrosion resistance caused by sensitization due to the precipitation of Cr carbonitrides. In order to obtain this effect, it is necessary to contain 0.05% or more of Ti. On the other hand, if the Ti content exceeds 0.35%, the toughness is significantly reduced due to the formation of coarse TiN, and the specified toughness cannot be obtained even if the technology of the present invention is applied. In addition, containing more than 0.35% of Ti generates coarse Ti carbonitrides in the casting process, resulting in surface defects, so it is not preferred in manufacturing. Therefore, the Ti content is 0.05% to 0.35%. The Ti content is preferably 0.10% or more. In addition, the Ti content is preferably less than 0.30%, and more preferably less than 0.15%.

[0055] N: 0.001~0.020%

[0056] If the N content exceeds 0.020%, the reduction in processability and corrosion resistance becomes significant. From the viewpoint of processability and corrosion resistance, the lower the N content, the better. When the N content is reduced to less than 0.001%, it requires a long time of refining, which leads to an increase in manufacturing cost and a decrease in productivity, so it is not preferred. Therefore, the N content is in the range of 0.001% to 0.020%. The N content is preferably 0.005% or more, and more preferably 0.007% or more. In addition, the N content is preferably 0.015% or less, and more preferably 0.012% or less.

[0057] γ I [%]: 65% or more

[0058] If γ shown in the following formula (1) I If the content of austenite in the metal structure is less than 65%, the amount of austenite in the metal structure is insufficient at the billet heating temperature before the start of hot rolling, so that a fine metal structure cannot be obtained. I [%] is 65% or more. I [%] is obtained by the following formula (1) for evaluating the stability of the austenite phase:

[0059] γ I [%]=24Ni+12Mn+6Cu-18Si-12Cr-12Mo+188 (1)

[0060] In addition, Ni, Mn, Cu, Si, Cr and Mo in Formula (1) represent the content (mass %) of each component, and the components not contained are represented by 0.

[0061] In the above formula (1), an austenite-forming element has a positive coefficient, and a ferrite-forming element has a negative coefficient, and each value is experimentally determined with reference to Castro's formula.

[0062] In the present invention, the remainder other than the above is Fe and inevitable impurities. Examples of the inevitable impurities include O (oxygen), and the content of O is permitted as long as it is 0.01% or less.

[0063] In addition to the above essential components, one or more components selected from the following Group A to Group C may be contained as necessary.

[0064] (Group A) One or more of Cu: 0.01 to 1.00%, Mo: 0.01 to 1.00%, W: 0.01 to 0.20%, Co: 0.01 to 0.20%

[0065] (Group B) One or more of V: ​​0.01 to 0.20%, Nb: 0.01 to 0.10%, Zr: 0.01 to 0.20%

[0066] (Group C) One or more of REM: 0.001 to 0.100%, B: 0.0002 to 0.0025%, Mg: 0.0005 to 0.0030%, Ca: 0.0003 to 0.0030%

[0067] Cu: 0.01~1.00%

[0068] Cu is an element that is particularly effective in improving corrosion resistance in a solution or when weakly acidic water droplets are attached. In addition, Cu has the effect of promoting the formation of an austenite phase. This effect is obtained by containing more than 0.01%, and the higher the Cu content, the better the effect. However, if Cu is contained in excess of 1.00%, the hot rolling workability may be reduced, resulting in surface defects. In addition, descaling after annealing may become difficult. Therefore, when Cu is contained, the Cu content is in the range of 0.01% to 1.00%. When Cu is contained, the Cu content is preferably more than 0.10%. In addition, when Cu is contained, the Cu content is preferably less than 0.50%.

[0069] Mo: 0.01~1.00%

[0070] Mo is an element that significantly improves the corrosion resistance of stainless steel. This effect is obtained by containing more than 0.01% Mo, and the higher the content, the better the effect. On the other hand, Mo has the effect of promoting the formation of ferrite phase. If the Mo content exceeds 1.00%, the specified amount of austenite phase is not fully generated during heating in the hot rolling process, and thus even if hot rolling and hot-rolled sheet annealing are performed under the conditions specified in the present invention, the desired metal structure cannot be obtained. Therefore, when Mo is contained, the Mo content is 0.01% to 1.00%. When Mo is contained, the Mo content is preferably 0.10% or more, and more preferably 0.30% or more. In addition, when Mo is contained, the Mo content is preferably 0.80% or less, and more preferably 0.50% or less.

[0071] W: 0.01~0.20%

[0072] W has the same effect as Mo in improving corrosion resistance. This effect is obtained by containing 0.01% or more of W. On the other hand, if W is contained in an amount exceeding 0.20%, the strength increases, and there is a case where the manufacturability is reduced due to an increase in the rolling load, etc. Therefore, when W is contained, the W content is in the range of 0.01% to 0.20%. When W is contained, the W content is preferably 0.05% or more. In addition, when W is contained, the W content is preferably 0.15% or less.

[0073] Co: 0.01~0.20%

[0074] Co is an element that improves toughness. This effect is obtained by containing 0.01% or more of Co. On the other hand, if the Co content exceeds 0.20%, there is a case where workability decreases. Therefore, when Co is contained, the Co content is in the range of 0.01% to 0.20%.

[0075] V: 0.01~0.20%

[0076] V forms carbonitrides with C and N, suppresses sensitization during welding and improves the corrosion resistance of the weld. This effect is obtained when the V content is 0.01% or more. On the other hand, if the V content exceeds 0.20%, there is a case where the workability and toughness are significantly reduced. Therefore, when V is contained, the V content is 0.01% to 0.20%. When V is contained, the V content is preferably 0.02% or more. In addition, when V is contained, the V content is preferably 0.10% or less.

[0077] Nb: 0.01~0.10%

[0078] Nb has the effect of refining the crystal grains. This effect is obtained by containing 0.01% or more of Nb. On the other hand, Nb also has the effect of increasing the recrystallization temperature. If the Nb content exceeds 0.10%, the annealing temperature required for sufficient recrystallization by hot-rolled sheet annealing becomes too high, and sometimes a metal structure with an average crystal grain size of less than 45μm cannot be obtained. Therefore, when Nb is contained, the Nb content is in the range of 0.01% to 0.10%. When Nb is contained, the Nb content is preferably less than 0.05%.

[0079] Zr: 0.01~0.20%

[0080] Zr has the effect of inhibiting sensitization by combining with C and N. This effect is obtained by containing 0.01% or more of Zr. On the other hand, if Zr is contained in an amount exceeding 0.20%, the workability is sometimes significantly reduced. Therefore, when Zr is contained, the Zr content is in the range of 0.01% to 0.20%. When Zr is contained, the Zr content is preferably 0.10% or less.

[0081] REM: 0.001~0.100%

[0082] REM (Rare Earth Metals) has the effect of improving oxidation resistance, and inhibits the formation of an oxide film (weld tempering color) at the weld and inhibits the formation of a Cr-deficient region directly below the oxide film. This effect is obtained by containing 0.001% or more of REM. On the other hand, if the REM content exceeds 0.100%, the manufacturing properties such as pickling properties during cold rolling annealing are sometimes reduced. Therefore, when REM is contained, the REM content is in the range of 0.001% to 0.100%. When REM is contained, the REM content is preferably 0.050% or less.

[0083] B: 0.0002~0.0025%

[0084] B is an element effective for improving the resistance to secondary processing brittleness after deep drawing. This effect is obtained by setting the B content to 0.0002% or more. On the other hand, if the B content exceeds 0.0025%, the workability and toughness sometimes decrease. Therefore, when B is contained, the B content is in the range of 0.0002% to 0.0025%. When B is contained, the B content is preferably 0.0003% or more. In addition, when B is contained, the B content is preferably 0.0012% or less.

[0085] Mg: 0.0005~0.0030%

[0086] In the steel containing Ti as in the present invention, if the Ti carbonitrides are coarsened, the toughness may be reduced. In this regard, Mg has the effect of inhibiting the coarsening of the Ti carbonitrides. This effect is obtained by containing 0.0005% or more of Mg. On the other hand, if the Mg content exceeds 0.0030%, the surface properties of the steel may deteriorate. Therefore, when Mg is contained, the Mg content is in the range of 0.0005 to 0.0030%. When Mg is contained, the Mg content is preferably 0.0010% or more. In addition, when Mg is contained, the Mg content is preferably 0.0020% or less.

[0087] Ca: 0.0003~0.0030%

[0088] Ca is an effective component for preventing nozzle clogging caused by crystallization of Ti-based inclusions that are easily generated during continuous casting. This effect is obtained by containing 0.0003% or more of Ca. On the other hand, if the Ca content exceeds 0.0030%, the corrosion resistance is sometimes reduced due to the formation of CaS. Therefore, when Ca is contained, the Ca content is in the range of 0.0003% to 0.0030%. When Ca is contained, the Ca content is preferably 0.0005% or more. In addition, when Ca is contained, the Ca content is preferably 0.0015% or less, and more preferably 0.0010% or less.

[0089] Next, the method for producing the ferritic stainless steel sheet of the present invention will be described.

[0090] The inventors of the present invention have repeatedly conducted in-depth research on a method for improving toughness in a ferritic stainless steel sheet. As a result, it was found that a steel billet having an appropriate steel composition is heated at preferably 1050 to 1250°C, preferably hot-rolled in 3 passes or more, and the obtained hot-rolled steel sheet is hot-rolled at 750 to 1050°C. Thus, a metal structure having an average crystal grain size of 45 μm or less and a Charpy impact value of 100 J / cm at -50°C is obtained. 2As a result, the toughness is greatly improved and the desired corrosion resistance is also obtained.

[0091] The reason why a hot-rolled annealed steel sheet having a fine metal structure can be obtained in this way will be described below.

[0092] Ferritic stainless steel hardly undergoes dynamic recrystallization during hot rolling, and tends to recover the processing deformation caused by rolling. Therefore, in the hot rolling of the prior art, the processing deformation introduced by rolling undergoes excessive recovery, and the processing deformation cannot be effectively maintained after hot rolling. As a result, the recrystallization sites become insufficient, and a fine recrystallized structure cannot be obtained in the subsequent hot rolled sheet annealing process.

[0093] Therefore, the inventors have conducted intensive research on the steel composition and hot rolling method to find an effective method for obtaining a fine structure after hot rolled sheet annealing. As a result, they have found that it is effective to control the steel composition, especially the contents of Si, Mn, Cr and Ni, within an appropriate range, heat the billet at an appropriate temperature in the hot rolling process, and form a two-phase structure of ferrite phase + austenite phase containing an austenite phase and perform hot rolling.

[0094] When the metal structure is a two-phase structure of ferrite phase + austenite phase, the heterophase interface between the ferrite phase existing before heating and the austenite phase generated during heating suppresses the coarsening of crystal grains, so a fine equiaxed structure is obtained in the stage before hot rolling. On this basis, by performing a predetermined hot rolling, the processing deformation that becomes a recrystallization site in the hot-rolled sheet annealing in the subsequent process is fully accumulated, and a fine metal structure is obtained by the hot-rolled sheet annealing in the subsequent process, which can show excellent toughness.

[0095] Specifically, the following scheme is proposed: the steel satisfying the above formula (1) is adjusted so that the contents of austenite-forming elements Ni and Mn are combined with respective positive coefficients of Ni and Mn and the contents of ferrite-forming elements Si and Cr are combined with respective negative coefficients of Si and Cr in a manner so that an austenite phase with a volume fraction of 65% or more is generated in the hot state before hot rolling, and the billet is heated at 1050-1250°C and then hot rolled.

[0096] In addition, the inventors have repeatedly conducted in-depth research on the preferred conditions for hot-rolled sheet annealing in the subsequent process. Hot-rolled sheet annealing is a process for recrystallizing the processed structure formed by hot rolling. Therefore, it is necessary to perform annealing at a temperature that produces sufficient recrystallization. However, when hot-rolled sheet annealing is performed at an excessively high temperature, although recrystallization occurs, the resulting recrystallized grains are significantly coarsened, and the specified fine structure cannot be obtained.

[0097] Therefore, the present inventors have investigated the relationship between the grain size of recrystallized grains and the annealing temperature in detail and have found that the formation of coarse recrystallized grains that reduce toughness can be suppressed by suppressing the hot-rolled sheet annealing temperature to 1050°C or less.

[0098] Hereinafter, each manufacturing condition will be described in detail.

[0099] First, molten steel having the above-mentioned component composition is melted by a known method such as a converter, an electric furnace, or a vacuum melting furnace, and a steel slab (billet) is formed by a continuous casting method or an ingot-casting method.

[0100] Billet heating temperature: 1050~1250℃

[0101] The steel billet is heated at 1050-1250°C and provided for hot rolling. The heating time of the above heating temperature is not particularly limited, and it is preferably heated for 1 to 24 hours. If the heating temperature is less than 1050°C, the generation ratio of the austenite phase becomes low, and a fine metal structure cannot be obtained, and excellent toughness cannot be obtained. On the other hand, if the heating temperature is too high, the oxide scale loss increases with the increase in oxidation mass, so the heating temperature of the steel billet is below 1250°C. Among them, when the steel billet is hot rolled, when the steel billet after casting is in a temperature range of 1050°C or above, it can be directly rolled without heating the steel billet plate.

[0102] The rough rolling conditions are not particularly limited. When the cast structure is effectively destroyed before the finish hot rolling, the refinement effect of the subsequent billet heating is further promoted, so it is preferable to set the cumulative reduction ratio of the rough rolling to 65% or more. Thereafter, the plate is rolled to a predetermined thickness by the finish hot rolling.

[0103] Hot rolled plate annealing temperature: 750~1050℃

[0104] In the present invention, hot rolled sheet annealing is performed after the hot rolling is completed. In the hot rolled sheet annealing, the rolling structure formed in the hot rolling process is recrystallized. In the present invention, rolling deformation is effectively applied in the hot rolling process, and the recrystallization sites are increased to suppress the coarsening of recrystallization in the hot rolled sheet annealing. In order to obtain this effect, it is necessary to perform hot rolled sheet annealing in the range of 750 to 1050°C. If the annealing temperature is less than 750°C, the recrystallization is insufficient, and residual stress caused by hot rolling deformation remains, and the flatness after hot rolling annealing cannot be maintained. On the other hand, if the annealing temperature exceeds 1050°C, the recrystallized grains are significantly coarsened, and the desired metal structure cannot be obtained. Therefore, the hot rolled sheet annealing temperature is in the range of 750°C to 1050°C. It is preferred that the hot rolled sheet annealing temperature is in the range of 750°C to 900°C. In addition, the holding time and method of hot rolled sheet annealing are not particularly limited, and can be implemented by any of box annealing (intermittent annealing) and continuous annealing.

[0105] The ferritic stainless steel sheet obtained above may be subjected to descaling treatment by shot blasting or pickling as required. In addition, grinding, polishing, etc. may be performed to improve the surface properties. In addition, cold rolling and cold rolled sheet annealing may be performed thereafter.

[0106] As described above, the ferritic stainless steel sheet having excellent toughness and excellent corrosion resistance according to the present invention is manufactured.

[0107] The metal structure of the ferritic stainless steel sheet obtained in the present invention is a ferrite single phase, or contains 3% or less (volume ratio) of martensite and retained austenite phase or both in total, and the remainder is a ferrite phase.

[0108] The Charpy impact value of the ferritic stainless steel sheet of the present invention at -50°C is 100 J / cm 2 Thus, by making the low-temperature toughness excellent, the occurrence of cracks in the flanged portion during processing of the thick flange having the flanged portion can be effectively suppressed, and the present invention can be fully applied to the thick flange having the flanged portion.

[0109] The plate thickness is not particularly limited, but is preferably a plate thickness that can be applied to thick flanges, and is therefore preferably 5.0 mm or more, more preferably 8.0 mm or more. The plate thickness is preferably 15.0 mm or less, more preferably 13.0 mm or less.

[0110] Example 1

[0111] Hereinafter, the present invention will be described in detail using examples.

[0112] The stainless steel melt having the composition shown in Table 1 was formed into a 100 kg steel billet by vacuum induction melting. Then, hot rolling was performed under the manufacturing conditions shown in Table 2 to form a hot rolled steel sheet having the finished plate thickness shown in Table 2. The hot rolled steel sheet was subjected to hot rolled sheet annealing to produce a hot rolled annealed steel sheet. It should be noted that the hot rolled sheet annealing was performed at the hot rolled sheet annealing temperature shown in Table 2 for 8 hours.

[0113] The hot-rolled annealed steel sheets obtained above were evaluated as follows.

[0114] (1) Evaluation of average crystal grain size

[0115] The average crystal grain size was measured by the EBSD (Electron Back Scattering Diffraction) method. The measurement conditions were a measurement magnification of 500 times and a step length of 0.4 μm. The data obtained was defined as a grain boundary with an orientation difference of 15° or more by the OIM (Orientation Imaging Microscopy) analysis software of TSLSolutions Co., Ltd., and the equivalent circle diameter was calculated. The value calculated from the average value of the equivalent circle diameter obtained was used as the average crystal grain size.

[0116] (2) Evaluation of Charpy impact value

[0117] A V-notch Charpy test piece based on JIS Z 2242 (2005) was taken from the center of the plate width of the hot-rolled annealed steel plate with the rolling direction as the long side while maintaining the plate thickness of the steel plate. The Charpy impact value at -50°C was measured based on JIS Z 2242 (2005). The Charpy impact value at -50°C was 100 J / cm 2 The above is considered qualified, and less than 100J / cm 2 As unqualified.

[0118] (3) Evaluation of corrosion resistance

[0119] From the hot-rolled annealed steel sheet, a 60×80 mm test piece was taken, and the surface was polished with #600 sandpaper, and the end surface and the back surface were sealed. The test piece was subjected to the salt spray cycle test specified in JIS H 8502. The salt spray cycle test is a cycle of salt spray (5 mass% NaCl, 35°C, spraying for 2 hours) → drying (60°C, 4 hours, relative humidity 40%) → wetting (50°C, 2 hours, relative humidity ≥ 95%), and three cycles were performed. The surface of the test piece after three cycles of the salt spray cycle test was photographed, and the rust area on the surface of the test piece was measured by image analysis. The rust rate was calculated from the ratio of the rust area to the area of ​​the rust area measurement part (rust area in the test piece / area of ​​the rust area measurement part) × 100 [%]). The rust area measurement part refers to the part of the test piece where the outer circumference of 15 mm is removed. It should be noted that the rust area is the area of ​​the rust part and the flow rust part. A rust rate of 10% or less was regarded as particularly excellent corrosion resistance and was rated as acceptable (◎), a rust rate of more than 10% and 25% or less was regarded as acceptable (○), and a rust rate of more than 25% was regarded as unacceptable (×).

[0120] The test results obtained above are shown in Table 2 together with the production conditions.

[0121]

[0122] Table 2

[0123]

[0124] The underline indicates that the

[0125] According to Table 1 and Table 2, No. 1 to 32 and 46, whose steel composition, hot rolling conditions and hot rolled sheet annealing conditions meet the scope of the present invention, obtain a fine metal structure with an average crystal grain size of 45 μm or less and obtain a specified Charpy impact value. The corrosion resistance of the obtained hot rolled annealed steel sheets was evaluated and it was found that the rust rate was less than 25%, which had sufficient corrosion resistance. In particular, No. 17 using steel A17 containing 0.95% Cu and No. 18 using steel A18 containing 0.88% Mo, obtained a further excellent corrosion resistance with a rust rate of less than 10%.

[0126] In addition, for the inventive examples No. 1 to 32 and 46, processing into a thick-walled flange shape with a flanging portion was attempted, and as a result, no cracking occurred and the predetermined flange shape was obtained. It should be noted that the results of the microstructure observation of the hot-rolled annealed steel sheets of the inventive examples all showed a ferrite single-phase structure, or a structure having a total volume ratio of one or both of martensite and retained austenite phases of 3% or less, and the remainder being a ferrite phase.

[0127] In No. 33 and No. 34 using Steel A1 and Steel A2, where the billet heating temperature is greater than the range of the present invention, although a specified amount of austenite phase is generated during heating in the hot rolling process and rolling is performed at a specified cumulative reduction rate, since the rolling temperature is too high, recovery of processing deformation occurs, resulting in insufficient introduction of recrystallization sites. Therefore, coarsening of recrystallized grains is easily generated in the hot rolled plate annealing process, and the specified Charpy impact value cannot be obtained.

[0128] In No. 35 and No. 36 using Steel A1 and Steel A2, in which the hot rolled sheet annealing temperature was higher than the range of the present invention, the generated recrystallized grains were remarkably coarsened, and as a result, the prescribed Charpy impact value could not be obtained.

[0129] Although the steel composition range is met, γ I In No. 37, No. 38 and No. 39 of steels B1, B2 and B3 which are smaller than the scope of the present invention, the prescribed hot rolling and hot-rolled sheet annealing were performed, but the austenite phase was not sufficiently generated during the heating in the hot rolling process. As a result, the metal structure was not sufficiently refined in the hot-rolled sheet annealing process, and the prescribed Charpy impact value could not be obtained.

[0130] In No. 40 using steel B4 having a Cr content greater than the range of the present invention, prescribed hot rolling and hot-rolled sheet annealing were performed, but the austenite phase was not sufficiently generated during heating in the hot rolling process. As a result, the metal structure was not sufficiently refined in the hot-rolled sheet annealing process, and the prescribed Charpy impact value could not be obtained.

[0131] In No. 41 using steel B5 having a Mn content exceeding the range of the present invention, predetermined hot rolling and hot rolled sheet annealing were performed, but MnS, which becomes a corrosion starting point, precipitated excessively, resulting in failure to obtain predetermined corrosion resistance.

[0132] In No. 42 using steel B6 having a Nb content exceeding the range of the present invention, the recrystallization temperature rises, so that the metal structure is not sufficiently refined, and the prescribed Charpy impact value cannot be obtained.

[0133] In No. 43 using the steel B7 having a Si content greater than that of the present invention, the average grain size of the metal structure was greater than 45 μm, and the prescribed Charpy impact value could not be obtained.

[0134] In No. 44 using steel B8 having a Ti content exceeding the range of the present invention, excessive Ti content resulted in the formation of coarse TiN, and the prescribed Charpy impact value could not be obtained.

[0135] In No. 45 using steel B9 without Ti addition, the recrystallization temperature increased, so the metal structure was not sufficiently refined, and the prescribed Charpy impact value could not be obtained.

[0136] In No. 47 using steel B10 having a Ni content smaller than the range of the present invention, the prescribed hot rolling and hot-rolled sheet annealing were performed, but the austenite phase was not sufficiently generated during heating in the hot rolling process. As a result, the metal structure was not sufficiently refined in the hot-rolled sheet annealing process, and the prescribed Charpy impact value could not be obtained.

[0137] Possibility of Industrial Application

[0138] The ferritic stainless steel sheet obtained in the present invention is particularly suitable for applications requiring excellent toughness, for example, application to flanges and the like.

Claims

1. A ferritic stainless steel sheet for flange processing having a thick wall and a flanged portion, comprising, by mass%, 0.001 to 0.020% C, 0.05 to 0.35% Si, 0.05 to 1.00% Mn, 0.04% or less P, 0.01% or less S, 0.001 to 0.300% Al, 10.0 to 13.0% Cr, 0.75 to 1.50% Ni, 0.05 to 0.35% Ti, and 0.001 to 0.020% N, and wherein a γ-gamma-ray diffraction reaction is performed according to the following formula (1): I [%] is 65% to 92%, and the remainder is composed of Fe and unavoidable impurities. Furthermore, the average crystal grain size of the metal structure is 45 μm or less. The plate thickness is 5.1mm or more. The Charpy impact value at -50°C measured in accordance with JIS Z2242 is 100 J / cm 2 above, The rust rate after three cycles of the salt spray cycle test specified in JIS H 8502 is 25% or less. γ I [%]=24Ni+12Mn+6Cu-18Si-12Cr-12Mo+188 (1) in, In the formula (1), Ni, Mn, Cu, Si, Cr, and Mo represent the content of each component in mass %, and components not contained are set to 0.

2. The ferritic stainless steel sheet according to claim 1, wherein: In addition to the above-mentioned component composition, one or more of Cu: 0.01 to 1.00%, Mo: 0.01 to 1.00%, W: 0.01 to 0.20%, and Co: 0.01 to 0.20% are contained in mass%.

3. The ferritic stainless steel sheet according to claim 1 or 2, wherein: In addition to the above-mentioned component composition, one or more of V: ​​0.01 to 0.20%, Nb: 0.01 to 0.10%, and Zr: 0.01 to 0.20% are contained in terms of mass%.

4. The ferritic stainless steel according to any one of claims 1 to 3, wherein In addition to the above-mentioned component composition, one or more of REM: 0.001 to 0.100%, B: 0.0002 to 0.0025%, Mg: 0.0005 to 0.0030%, and Ca: 0.0003 to 0.0030% are contained in terms of mass%. 5 . The ferritic stainless steel according to claim 1 , wherein the plate thickness is 8.0 mm or more.

6. A method for producing a ferritic stainless steel sheet, the method for producing a ferritic stainless steel sheet according to any one of claims 1 to 5, comprising: A hot rolling process of heating the steel slab having the above composition at 1050-1250° C. and then hot rolling the steel slab; and The hot rolled steel sheet obtained in the hot rolling step is subjected to a hot rolled sheet annealing step at 750 to 1050°C.

Citation Information

Patent Citations

  • corselette

    CA300030A

  • Stainless steel sheet excellent in toughness and production method thereof

    JP2016191150A

Cited By

  • High-strength bcc structure corrosion-resistant alloy plate with ultrahigh low-temperature toughness and preparation method thereof

    CN122791264A